Memory Devices: MoS2/Polymer Heterostructures Enabling Stable Resistive Switching and Multistate Randomness (Adv. Mater. 42/2020). Issue 42 (20th October 2020) - Chai, Jianwei; Tong, Shiwun; Li, Changjian; Manzano, Carlos; Li, Bing; Liu, Yanpeng; Lin, Ming; Wong, Laimun; Cheng, Jianwei; Wu, Jing; Lau, Aaron; Xie, Qidong; et al.
Abstract : In article number 2002704, Henry Medina, Ming Yang, Shijie Wang, Dongzhi Chi, and co‐workers report a ReRAM cell with outstanding cumulative probabilities using a MoS2 /polymer heterostructure. Moreover, the high resistance state is determined to be an excellent source of multistate randomness. Thus, a process for the production of high‐performance ReRAM devices is presented, which sheds light on their application as random number generation.